Bilateral Sanyinjiao acupuncture reduces the dose of intravenous remifentanil in labor analgesia - T.T. Wang; C. Liang; F.L. Kong; B. Dong; C. Feng (IMR Press, 2020)
This study aims to evaluate the effects of intravenous analgesia using remifentanil combined with Sanyinjiao acupuncture in childbirth. A total of 150 women who delivered their babies naturally were selected. Among these, 100 women willing to undergo labor analgesia and were full-term and with single child, cephalic presentation, and without pregnancy complications were randomly divided into an intravenous injection group (IV) and a combined injection group (CI), while the remainder comprised the control group (C). After the patients entered the active phase of labor, remifentanil was intravenously infused. Patients in group CI were injected with 2 ml of 1% lidocaine into the bilateral Sanyinjiao acupoint. After analgesia began, pain score, mean arterial pressure, and heart rate in group IV and group CI were significantly lower than in group C (p < 0.05). The dose of remifentanil was significantly lower in group CI than in group IV (p < 0.05); however, there was no significant difference in the duration of labor and neonatal score among the three groups (p > 0.05). Neither excessive sedation nor respiratory depression occurred. Sanyinjiao acupoint injection combined with intravenous infusion of remifentanil reduced the amount of opioids and the risk for serious adverse reactions.